All you need is a good idea! : - Heyman, Jay H. (Wiley, 2008)
In All You Need Is a Good Idea, Jay Heyman shows you how to create powerful marketing and advertising ideas that will dramatically increase sales for your business. Perfect for entrepreneurs and small business owners?or operators of any size business, for that matter?this valuable marketing resource will help any business stand out in the marketplace, build bigger market share, gain publicity, and scare the pants off the competition. This book is the perfect guide to creating truly powerful marketing messages